Development and application of a novel mass spectrometry ionization source for biological chemistry - Rhodri Owen (2022)
Since its development, electrospray ionization (ESI) for the analysis of thermally labile, polar compounds and particularly biomolecules has been extremely useful. Not all compounds can be easily protonated and electron ionization (EI) is still a widely used ionization method for compounds like hydrocarbons. However, the low-pressure environment of the EI source requires complex and expensive vacuum systems and inlets. Therefore, a source which can ionises non-polar compounds while operating at atmospheric pressure would be highly advantageous. In this thesis I have undertaken development and characterisation of four prototype atmospheric pressure glow discharge ionization sources for the analysis of compounds not normally amiable to ionization by conventional atmospheric pressure ionization sources. A helium micro-glow discharge source (“Prototype V”) operated using a direct current power supply was studied and its discharge characterised. Its current-voltage relationship increased linearly which is typical of the abnormal glow regime while thermal imaging showed it had a “cold” discharge. Prototype V was successfully interfaced with a Xevo G2-S time-of-ﬂight and a Xevo TQ-S triple quadrupole (Waters Corp, Wilmslow, UK) and used with a range of sample introduction methods, initially a solids probe, but later APCI and ESI probes. These probes enabled prototype V to readily integrate with separation sciences; speciﬁcally liquid chromatography was demonstrated for complex mixture analysis. Prototype V exhibited high analytical sensitivity in the nanogram range in both positive and negative modes and could ionize a wide range of compound chemistries from polar to non-polar. In particular it showed sensitivity to non-polar compounds in negative-ion mode when compared to ESI. This gives the source the potential to operate in conjunction with a range of sample inlets and in combination with other ionization techniques as part of a multimodal platform to analyse the widest range of samples and a step towards a universal source.